A formal ontology-based spatiotemporal mereotopology for integrated product design and assembly sequence planning. Issue 3 (August 2015) - Gruhier, Elise; Demoly, Frédéric; Dutartre, Olivier; Abboudi, Said; Gomes, Samuel
Abstract This paper introduces the development of a formal ontology based on spatiotemporal mereotopology in the context of integrated assembly design and sequence planning. The main objective is to make assembly information accessible and exploitable by information management systems and computer-aided X tools in order to support product architects and designer's activities. Indeed product design information and knowledge as well as the related assembly sequence require a semantic and logical foundation in order to be managed consistently and processed proactively. In this context, product relationships are considered and described in the part-whole theory supported by mereology and its extension, mereotopology. Firstly, a literature survey on formalisms in assembly-oriented design, mereotopological theories and spatiotemporal ontologies is presented so as to highlight the current research issue. Then, a mathematical description approach of product relationships based on mereotopology and temporal relationships is introduced. Built on this, an ontological development of the proposed theory using description logic rules is proposed. Finally, a mechanical assembly, as a case study, is introduced to illustrate the relevance of the proposed ontology.